Female copulation song is modulated by seminal fluid - Peter Kerwin (Nature Portfolio, 2020)
Male fruitflies sing a patterned wing song during courtship. Here, the authors show that females sing a distinct song during copulation, which is controlled by sex-specific neurons, depends on seminal fluid from the male accessory gland and modulates latency of female remating with subsequent males.